School principals and racism: responding to Aveling. Issue 2 (3rd March 2016) - Charles, Claire; Mahoney, Caroline; Fox, Brandi; Halse, Christine
Abstract : This study responds to Nado Aveling's call in 'Anti-racism in Schools: A question of leadership?' ( Discourse: Studies in the Cultural Politics of Education, 2007, 28(1), 69–85) for further investigation into racism in Australian schools. Aveling's interview study concluded that an overwhelming number of school principals denied the presence of racism in their schools, and that there were no discernible differences in how principals in different schools constructed racism. In contrast, our research found that school principals' constructions of cultural racism are strongly influenced by their school contexts. We elucidate these differences examining the various intersections between race, class and religion deployed by principals in different sites, and argue for the utility of examining and theorising cultural racism using an intersectional approach. By bringing context into our analysis we provide a more nuanced insight into the different ways in which racism is constituted and understood by Australian school principals.